Effects of nitrogen fertilizer application on saline-alkali land cotton in China quantified using meta-analysis and regression analysis - Yang, Changkun; Liu, Hongguang; Gong, Ping; Li, Pengfei; Qiao, Xiang; Li, Zhijie; Jin, Hua; Zhang, Qian; Xia, Hanji (International Journal of Agricultural and Biological Engineering, 2023)
Nitrogen fertilizer application is an important means to promote cotton production in saline-alkali land. A meta-analysis and regression analysis of 49 peer-reviewed studies were conducted using yield data (373 data points), dry matter accumulation (114 data points), and water use efficiency (157 data points) to quantify the effect of nitrogen fertilizer on the yield, dry matter accumulation, and water use efficiency of cotton in saline-alkali land in China for different planting management practices and different growing environments. The results showed that the nitrogen application significantly improved the yield, dry matter accumulation, and water use efficiency by 34.11%, 36.27%, and 33.87%, respectively, compared with no nitrogen application. The largest improvements in the yield, dry matter accumulation, and water use efficiency occurred in areas where saline-alkali land had been improved for many years, in Eastern China, South Central China, and Northwest China (areas with annual average precipitation ≤200 mm or >800 mm, and annual average evaporation ≤800 mm or >2400 mm), in areas with trickle irrigation, and fields with a planting density of 100 000 to 250 000 plants/hm2. Cotton exhibited the optimal response to nitrogen application at a rate of 300-375 kg/hm2, a basal application ratio of 20%-40%, and top-dressing in the cotton bud, flowering boll, and full boll stages. The effect of nitrogen application increased as the salinity increased. A suitable nitrogen application rate, top-dressing ratio, and top-dressing period are crucial for increasing cotton production in saline-alkali land, although environmental differences and planting measures have to be considered. This study provided information on the correct application of nitrogen fertilizer to maximize its benefits and suggests controlling nitrogen fertilizer inputs in agriculture to protect the soil environment and ensure sustainable agricultural development. Keywords: meta-analysis, regression analysis, nitrogen fertilizer application, saline-alkali land, cotton DOI: 10.25165/j.ijabe.20231604.7802 Citation: Yang C K, Liu H G, Gong P, Li P F, Qiao X, Li Z J, et al. Effects of nitrogen fertilizer application on saline-alkali land cotton in China quantified using meta-analysis and regression analysis. Int J Agric & Biol Eng, 2023; 16(4): 145-158.